Alkaline phosphatase dual‐binding sites for collagen dictate cell migration and microvessel assembly in vitro. Issue 1 (3rd August 2020) - Guerreiro, Susana G.; Unger, Ronald E.; Cerqueira, Nuno M. F. S. A.; Sartoris, Anne; Martins, Maria J.; Barbosa, Mário A.; Soares, Raquel; Granja, Pedro L.; Kirkpatrick, Charles J.
Abstract: Interactions between cell types, growth factors, and extracellular matrix components involved in angiogenesis are crucial for new vessel formation leading to tissue regeneration. This study investigated whether cocultures of fibroblasts and endothelial cells (ECs; from macro‐ or microvasculature) play a role in the formation of microvessel‐like structures by ECs, as well as modulate fibroblast differentiation and growth factors production (vascular endothelial cell growth factor, basic fibroblast growth factor, active transforming growth factor‐β1, and interleukin‐8), which are important for vessel sprouting and maturation. Data obtained revealed that in vitro coculture systems of fibroblasts and human ECs stimulate collagen synthesis and growth factors production by fibroblasts that ultimately affect the formation and distribution of microvessel‐like structures in cell cultures. In this study, areas with activated fibroblasts and high alkaline phosphatase (ALP) activity were also observed in cocultures. Molecular docking assays revealed that ALP has two binding positions for collagen, suggesting its impact in collagen proteins' aggregation, cell migration, and microvessel assembly. These findings indicate that bioinformatics and coculture systems are complementary tools for investigating the participation of proteins, like collagen and ALP in angiogenesis. Abstract : Our results suggest a new role for alkaline phosphatase (ALP) in the alignment of the collagen proteins in coculture systems of human endothelial cells and fibroblasts that, in turn, may dictate cell migration and microvessel assembly. Dimers of ALP have two binding positions for collagen, suggesting they might be important for the aggregation of the collagen proteins in coculture systems.